Simultaneous bilateral total hip arthroplasty dislocation with unilateral foot drop following closed reduction. (30th December 2016) - Smith, Alexander Edward; Buckle, Christopher; Hester, Thomas; Slater, Guy
Abstract : Dislocation following primary and revision arthroplasty is a well-recognised complication with an estimated incidence rate of 0.2–10%. We present a rare case of simultaneous bilateral total hip replacement dislocation, complicated by unilateral foot drop following closed reduction, with no improvement in neurological function at 6-month follow-up.